The Role of Digital Resilience as a Moderator in Digital Banking Usage Behavior within the Modified UTAUT2 Model - Anthony Anthony; Erwin Setiawan Panjaitan; Sofiana Nurjanah (Poltanesa, 2026)
This study aims to analyze digital banking usage behavior by developing a Modified UTAUT2 model that integrates trust and digital resilience within the context of Medan City, Indonesia. A quantitative causal approach was employed using survey data collected from 316 active digital banking users selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.1 to evaluate both measurement and structural models. The results indicate that performance expectancy, effort expectancy, social influence, and trust significantly influence behavioral intention, while behavioral intention and habit significantly influence use behavior, with habit emerging as the strongest predictor of actual usage. Facilitating conditions were not found to significantly affect use behavior. Digital resilience did not moderate the relationships between behavioral intention, facilitating conditions, habit, and use behavior in the main model; however, it demonstrated significant direct effects on both behavioral intention and use behavior in the exploratory model. Additionally, digital resilience negatively moderated the relationship between performance expectancy and behavioral intention, suggesting that highly resilient users rely less on instrumental performance perceptions in forming intention. The model exhibits moderate to high predictive power, explaining 47.6 percent of behavioral intention and 68.3 percent of use behavior. The findings extend UTAUT2 by highlighting the role of adaptive capacity in digital financial service adoption and provide practical implications for strengthening trust, usability, and habitual engagement in digital banking services.